John Q. Flynn Flynn's Digest of the City Ordinances, Together with the Constitutional Provisions, Acts of the General Assembly, and Decisions of the Courts Relative to the Government of the City of New Orleans 545 (1896) - (:unkn) unknown (My University, 1893)
1342: It shall be unlawful for any one to sell, or lease, or give through himself or any other person, any pistol, dirk, bowie knife, toy pistol for which cartridges are used, or any other dangerous weapon which may be carried concealed, to any person under the age of eighteen years.
Keywords: TRANSFER - MINORS